Social adaptation of the indigenous peoples of the Russian North to the changing ice environment. - Gashiliva , Ludmila (Arctic Portal, 2011)
Dr. Ludmila Gashiliva Head of the Institute of the Peoples of the North, and Tatiana Bulgakova, Professor of the Institute of the Peoples of the North, Russian State Pedagogical University talk here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. The sessions name is Humanity, communities, Minds, Perceptions and Knowledge on Ice. Please click on the link above to see the video.